Navigating the Path to Sustainability: The Interplay of Entrepreneurial Knowledge, Creativity, and Motivation in the Micro, Small, and Medium Enterprises (MSMEs) Landscape - Salsabila, Putri; Hastin Umi Anisah (Open Access Indonesia Journal of Social Sciences, 2024)
The sustainability of Micro, Small, and Medium Enterprises (MSMEs) is crucial for economic growth and development, particularly in emerging economies. This study investigates the influence of entrepreneurial knowledge, creativity, and motivation on the sustainability of MSMEs operating within the culinary sector. The research employs a quantitative approach, utilizing survey data collected from 30 MSME owners and employees at Gatsu Food Square in Banjarmasin, Indonesia. The data analysis involves validity and reliability tests, normality checks, and regression analysis to examine the relationships between the variables. The findings reveal that entrepreneurial knowledge has a positive and significant impact on business sustainability. However, creativity and entrepreneurial motivation do not exhibit a statistically significant influence on sustainability in this specific context. The study underscores the critical role of entrepreneurial knowledge in fostering sustainable businesses. It suggests that while creativity and motivation are important entrepreneurial attributes, their direct impact on sustainability may be contingent upon other factors or require further investigation. The research offers valuable insights for policymakers, MSME support organizations, and entrepreneurs themselves in promoting sustainable business practices within the MSME sector.